2004
DOI: 10.1539/joh.46.374
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Related Factors Associated with Visiting a Doctor for a Medical Diagnosis after a Worksite Screening for Diabetes Mellitus in Japanese Male Employees

Abstract: Work-Related Factors Associated withVisiting a Doctor for a Medical diagnosis after a Worksite Screening for Diabetes Mellitus in Japanese Male Employees: Kaho TSUDA, et al. Department of Hygiene and Preventive Medicine, Okayama University Graduate School of Medicine and Dentistry-This paper aims to investigate the work-related factors that affect whether Japanese male employees will seek a medical diagnosis after being screened for diabetes mellitus. Participants in this study received a questionnaire two mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Its probability is assumed at 40.0% based on the literature [15, 16] and of the opinion of an expert committee set up for the purpose of this study, whose members are acknowledged in the “Acknowledgements” section. Those who avoid further examination follow the Markov model.…”
Section: Methodsmentioning
confidence: 99%
“…Its probability is assumed at 40.0% based on the literature [15, 16] and of the opinion of an expert committee set up for the purpose of this study, whose members are acknowledged in the “Acknowledgements” section. Those who avoid further examination follow the Markov model.…”
Section: Methodsmentioning
confidence: 99%
“…For other work environmental factors, low job control has been reported to be associated with having less access to medical care among Japanese male employees, although it was specific to one situation (i.e., after diabetes screening in the workplace) [36]. This empirical finding also suggests that organizational justice has a potential effect on RSMC because it captures more basic elements of the social structure within which task-level job characteristics, such as job demands and job control, are operating [37].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as we used claims data among employees, employment patterns or environments could affect physician visit patterns. For example, Tsuda et al . reported that employees who could comfortably take a day off or time off work, those with a high level of psychological job control and those referred by occupational health professionals were more likely to visit a doctor after worksite screening for diabetes mellitus, whereas those who worked ≥61 h per week were less likely to visit.…”
Section: Discussionmentioning
confidence: 99%